Bis-Schiff bases of 2, 2′-dibromobenzidine as efficient corrosion inhibitors for mild steel in acidic medium. Issue 8 (28th January 2020) - Arshad, Ifzan; Saeed, Aamer; Channar, Pervaiz Ali; Shehzadi, Syeda Aaliya; Ahmed, Muhammad Naeem; Siddiq, Muhammad
Abstract : The inhibitory effect of three new bis-Schiff bases on mild steel corrosion in 0.5 M HCl was studied by the weight loss method and the electrochemical method. Abstract : In this work, three new bis-Schiff bases, namely 1, 1′-(2, 2′-dibromo-[1, 1′-biphenyl]-4, 4′-diyl)bis( N -phenylmethanimine) (BNSB01 ), 1, 1′-(2, 2′-dibromo-[1, 1′-biphenyl]-4, 4′-diyl)bis( N -(4-bromophenyl)methanimine) (BNSB02 ) and 4, 4′-(((2, 2′-dibromo-[1, 1′-biphenyl]-4, 4′-diyl)bis(methanylylidene))bis(azanylylidene))diphenol (BNSB03 ), were synthesized. These Schiff bases were evaluated for their corrosion inhibition ability on mild steel specimens in 0.5 M HCl by using electrochemical and weight loss techniques. The inhibition performance was found to increase with an increase in the inhibitor concentration and decrease with an increase in temperature. The results revealed that the synthesized compounds followed the Langmuir isotherm model and were efficient mixed-type inhibitors. The electrochemical impedance studies also indicated that with a rise in the concentration of inhibitors, the charge transfer resistance increased. The surface morphology of the inhibited and uninhibited specimens was examined using scanning electron microscopy (SEM). The efficiency of the compounds was in the order BNSB02 > BNSB03 > BNSB01 . All the results obtained were in good correlation with each other.